The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.joc.5b00577
|View full text |Cite
|
Sign up to set email alerts
|

Amine Detection with Distyrylbenzenedialdehyde-Based Knoevenagel Adducts

Abstract: Eight acceptor-substituted distyrylbenzene (DSB) derivatives were obtained by postfunctionalization of dialdehyde precursor 1 using Knoevenagel condensation. Solubility in a water/THF 9:1 mixture was achieved through the addition of branched oligoethylene glycol side chains. The acceptor compounds discriminate primary and secondary amines in aqueous solution. The fluorescence responses were analyzed by the multivariate analysis of variance (MANOVA) protocol, a statistical tool. In contrast to 1, the adducts sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Optical methods, such as UV-Vis or fluorescence spectroscopy, are particularly attractive as analytical tools due to their simplicity, sensitivity, low cost, ease of miniaturization, and potential for in-situ measurement. Accordingly, they have been used for determination of thiols like cysteine, homocysteine, glutathione, H 2 S [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], and (biogenic) amines, namely phenethylamine, tyramine, histamine, ethylamine, methylamine, agmatine, isopentylamine, propylamine, and putrescine [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], by using specific indicator dyes that exhibit different spectral characteristic when exposed to these analytes. To mention some of the indicator dyes used for the detection of thiols, Deng et al developed a colorimetric and ratiometric fluorescent probe with diketopyrrolopyrrole (DPP) fluorophore, which (in the presence of cysteine) changed from purple to yellow, whereas the fluorescence changed from red to yellow [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optical methods, such as UV-Vis or fluorescence spectroscopy, are particularly attractive as analytical tools due to their simplicity, sensitivity, low cost, ease of miniaturization, and potential for in-situ measurement. Accordingly, they have been used for determination of thiols like cysteine, homocysteine, glutathione, H 2 S [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], and (biogenic) amines, namely phenethylamine, tyramine, histamine, ethylamine, methylamine, agmatine, isopentylamine, propylamine, and putrescine [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], by using specific indicator dyes that exhibit different spectral characteristic when exposed to these analytes. To mention some of the indicator dyes used for the detection of thiols, Deng et al developed a colorimetric and ratiometric fluorescent probe with diketopyrrolopyrrole (DPP) fluorophore, which (in the presence of cysteine) changed from purple to yellow, whereas the fluorescence changed from red to yellow [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DAAD compound has been prepared by Knoevenagel condensation of [9,9′-bianthracene]-10,10′-dicarbaldehyde and malononitrile under the catalysis of weak alkali (Scheme ). The molecular structures and purities are confirmed by 1 H and 13 C NMR spectroscopies and mass spectroscopy (see the synthesis details and full molecular characterizations in the Experimental Section). DAAD shows almost identical absorption profiles in polar and nonpolar solvents, with the maximum absorption peaks at 440 nm.…”
Section: Resultsmentioning
confidence: 92%
“…Optical sensors have been applied to determine biogenic amines in various food and beverages such as histamine, tyramine, ethylamine, putrescine, agmatine, isopentylamine, methylamine and propylamine by using speci c indicator dyes that exhibit di erent spectral characteristics when exposed to these analytes (Kumpf et al (2015); (Mastnak et al, 2018); Nedeljko et al (2017); Rawat et al (2017)). Malik et al (2016) reported the biogenic amines determination in liquid samples where this study synthesized the water-soluble cationic conjugated polymer using [9,9-bis(6'-methylimidazoliumbromide)hexyl)-uorene-co-4,7-(2,1,3-benzothiadiazole)](PFBT-MI) and combined it with a surfactant in order to acquire aggregates, which enabled the spermine detection.…”
Section: Optical Sensorsmentioning
confidence: 99%